How to Read the Qur'an : A New Guide, with Select Translations - Ernst, Carl W., 1950- (Book collections on Project MUSE., 2011)
This book offers a compact introduction and reader's guide for anyone, non-Muslim or Muslim, who wants to know how to approach, read, and understand the text of the Qur'an. Using a chronological reading of the text according to the conclusions of modern scholarship, Ernst offers a nontheological approach that treats the Qur'an as a historical text that unfolded over time, in dialogue with its audience, during the career of the Prophet Muhammad.